Estimasi Hilang Panas Alamiah Pada Manifestasi Mata Air Panas Desa Pinaesaan Kecamatan Tompaso Baru Kabupaten Minahasa Selatan - Putri Isaura Christoffel; Armstrong F. Sompotan; Jefferson Polii (Jurnal FisTa : Fisika dan Terapannya, 2023)
Geothermal energy is a source of heat energy stored in rocks and fluids contained below the earth's surface. One area that has geothermal potential in North Sulawesi is Pinaesaan Village, Tompaso Baru District. Around the village of Pinaesaan, geothermal manifestations are found, one of which is a hot spring. In determining the prospect of geothermal potential in an area, it is necessary to conduct research on surface manifestations. One of the steps taken in the study of surface manifestations is the calculation of natural heat loss (heat loss) at the research site. The method used in this study is direct measurement in the field by measuring air temperature, manifestation temperature and area of manifestation, which will then be processed through heat loss calculations. Based on the research, the average temperature of the hot spring manifestations in Pinaesaan village is the temperature manifestation 71,3˚C and air temperature 24,7˚C and the area of manifestation 2,94 m2. The value of heat loss is 0,0185 MW, and the speculative resource is 0.185 MW.